High Rates of Uncontrolled Blood Pressure in Malawian Adults Living with HIV and Hypertension - Risa M. Hoffman; Florence Chibwana; Daniel Kahn; Ben Allan Banda; Linna Phiri; Mayamiko Chimombo; Chiulemu Kussen; Hitler Sigauke; Agnes Moses; Joep J. van Oosterhout; Sam Phiri; Jesse W. Currier; et al. (Ubiquity Press, 2021)
Background: Hypertension is among the most commonly diagnosed non-communicable diseases in Africa, and studies have demonstrated a high prevalence of hypertension among individuals with HIV. Despite high prevalence, there has been limited attention on the clinical outcomes of hypertension treatment in this population. Objective: We sought to characterize rates of and factors associated with blood pressure control over one year among individuals on antiretroviral therapy (ART) and antihypertensive medications. Methods: We performed a prospective observational cohort study at an HIV clinic in Malawi. We defined uncontrolled hypertension as a systolic blood pressure ≥140 mm Hg and/or diastolic blood pressure ≥90 mm Hg at two or more follow-up visits during the year, while controlled hypertension was defined as <140 mm Hg systolic and <90 mm Hg diastolic at all visits, or at all but one visit. We calculated an antihypertensive non-adherence score based on self-report of missed doses at each visit (higher score = worse adherence) and used rank sum and chi-square tests to compare sociodemographic and clinical factors (including adherence) associated with blood pressure control over the year. Results: At study entry, 158 participants (23.5%) were on antihypertensive medication; participants had a median age of 51.0 years, were 66.5% female, and had a median of 6.9 years on ART. 19.0% (n = 30) achieved blood pressure control over the year of follow-up. Self-reported non-adherence to hypertension medications was the only factor significantly associated with uncontrolled blood pressure. The average non-adherence score for those with controlled blood pressure was 0.22, and for those with uncontrolled blood pressure was 0.61 (p = 0.009). Conclusions: Adults living with HIV and hypertension in our cohort had low rates of blood pressure control over one year associated with self-reported non-adherence to antihypertensive medications. Given the high prevalence and incidence of hypertension, interventions to improve blood pressure control are needed to prevent associated long-term cardio- and cerebrovascular morbidity and mortality.